Elements of Interaction in Self and Human Beings Based on the Qur'an in the Learning of 21st Century Islamic Education / Elemen Interaksi Dalam Diri Dan Sesama Manusia Berasaskan Al-Quran Dalam Pembelajaran Abad Ke-21 Pendidikan Islam - Wan Mohamad, Wan Mariana; Mat Teh, Kamarul Shukri; Wan Abdullah, Wan Ali Akbar (Sains Humanika, 2021)
This study aims to identify the expert consensus on the items for the elements of interaction in self and human beings for communication skills in 21st Century Learning (PAK21) Islamic Education. This study uses the Fuzzy Delphi Method (FDM) application in the process of designing and developing the Islamic Education PAK21 Model based on the analysis of Quranic content. The data were collected using a questionnaire instrument that was given to 11 experts in the field of Tafsir al-Quran and Islamic Education who have served for more than 10 years. The findings of the study show that all 12 items of interaction in self and fellow human beings have been approved by experts. The items meet the acceptance conditions with the threshold value (d) is less than 0.2, the percentage of expert agreement is more than 75% and the value of defuzzification is more than 0.5. Implications of the study led to the formation of Model of Interaction Elements in Self and Human Beings for Communication Skills PAK21 Islamic Education.